Orbital Angular Momentum Multiplexing in Highly Reverberant Environments - Chen, Xiaoming; Xue, Wei; Shi, Hongyu; Yi, Jianjia; Sha, Wei E. I. (IEEE microwave and wireless components letters, 2020)
Previous studies on orbital angular momentum (OAM) communication mainly considered line-of-sight (LOS) environments. In this letter, however, it is found that OAM communication with high-order modulation can be achieved in highly reverberant environments by combining the OAM multiplexing with a spatial equalizer. The OAM multiplexing exhibits comparable performance of the conventional multiple-input-multiple-output (MIMO) system.